Protective effects of acehnese traditionally fermented coconut oil (Pliek U Oil) and its residue (Pliek U) in ointment against UV light exposure: studies on male Wistar rat skin (Rattus novergicus) - Earlia, Nanda; Bulqiah, Mikyal; Muslem, Muslem; Karma, Taufiq; Suhendra, Rivansyah; Maulana, Aga; Amin, Mohamad; Sasmita, Novi Reandy; Idroes, Ghazi Mauer; Prakoeswa, CRS; Suhartono, Eko; Khairan, Khairan; et al. (Penerbit Universiti Kebangsaan Malaysia, 2021)
A protective effect of Acehnese traditionally fermented coconut oil (Pliek U oil) and its residue (Pliek U) have been studied against UVB radiation. The research was performed by preparing the active ingredient in ointment formulation and protective test in male Wistar rat skin (Rattus novergicus). Four different extraction methods were done to produce four active ingredients, that are Pliek U oil (PUO), ethanolic Pliek U oil extract (EPUOE), ethanolic Pliek U extract (EPUE), and ethanolic hexane residue Pliek U extract (EHRPUE). The protective effect was determined based on the erythema index (EI), melanin index (MI), and level of protein oxidation parameters. The protective level from each active ingredient was studied by PCA analysis. The result showed that the active ingredient could inhibit the redness and protein oxidation in skin tissue. PCA results show that concentration (20 v. 40%) does not affect the protection level of the active ingredients of Pliek U oil, but it does affect the one of Pliek U. Therefore, these active ingredients are potential for sunscreen application.